“ANÁLISE FACIAL SUBJETIVA”: UM NOVO MÉTODO DE DIAGNÓSTICO (REMUNOM, 2023)
This article aims, through a bibliographical review, to carry out an evaluation of the Subjective Facial Analysis, addressing its use and indications, in addition to the factors that most influence the aesthetics of the facial profile. The perception of beauty is subjective and culturally influenced, so facial analysis becomes essential for successful orthodontic treatment. The information obtained through this analysis guides the procedures that must be carried out so that beauty is valued and preserved, therefore the effects caused on the face must be critically analyzed. Therefore, it is concluded that the "Subjective Facial Analysis" is a valid and efficient method in the classification of the Facial Pattern. It constitutes a valuable resource for the diagnosis and planning of orthodontic treatment and should be used in association with conventional cephalometric analyses. Facial attractiveness depends on typology. The most attractive faces are those of individuals with Pattern I. Pattern II males and Pattern III females are considered aesthetically displeasing. On the other hand, Pattern III men and Pattern II women are considered aesthetically acceptable, demonstrating that the increase in facial convexity in females and the reduction in males is acceptable. The lips, nose and chin are the most important structures in determining the degree of attractiveness of the facial profile.